Chicken TBK1 interacts with STING and is involved in IFN-β signaling regulation. (December 2017) - Cheng, Yuqiang; Ma, Jingjiao; Liu, Yunxia; Gao, Quanxin; Yan, Yaxian; Wang, Hengan; Ding, Chan; Sun, Jianhe
Abstract: TANK-binding kinase 1 (TBK1) is an essential serine/threonine-protein kinase required for the Toll-like receptor (TLR)- and retinoic acid-inducible gene I (RIG-I) -mediated induction of type I IFN. Through endogenous Co-IP and LC-MS/MS, we identified chicken TBK1 (chTBK1) as a chSTING-interactive protein. Through exogenous Co-IP assay in transfected cells, we confirmed the interaction between chSTING and chTBK1. To better understand the biological role of chTBK1 in the chSTING-mediated IFN pathway, we cloned the chTBK1 and investigated its biological functions. Quantitative RT-PCR showed that chTBK1 mRNA was widely expressed in different tissues. The overexpression of chTBK1 in DF-1 cells induced the expression of IFN-β and ISGs and inhibited AIV viral replication. We identified indispensable domains of chTBK1 on IFN-β production via the generation of various chTBK1 mutant forms. Together, we identified the chTBK1 as a chSTING interactive protein and concluded that chTBK1 is involved in chSTING-triggered IFN-β signaling in chicken cells. Highlights: Chicken TBK1 (chTBK1) was identified as a chSTING-interactive protein. ChTBK1 was cloned, and its biological function in IFN-β activation was investigated. The expression of chTBK1 augments the IFN response and reduces H9N2 AIV replication in DF-1 cells. The NS1 of H9N2 AIV counteracts the IFN-β activation mediated by chTBK1 overexpression.